2017
DOI: 10.1371/journal.pone.0170939
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Aortic Valve and Left Ventricular Parameters Related to the Severity of Myocardial Fibrosis in Patients with Severe Aortic Valve Stenosis

Abstract: ObjectiveThis study investigated the morphological and functional characteristics of the aortic valve and the left ventricular (LV) systolic functional parameters and myocardial mass related to the severity of myocardial fibrosis (MF) in patients with severe aortic valve stenosis (AS).Materials and MethodsWe retrospectively enrolled 81 patients (48 men; mean age: 59±12 years) with severe AS who underwent transthoracic echocardiography (TTE), cardiac computed tomography (CCT), and cardiovascular magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…13 The mechanisms underlying the association of VAC with post-TAVI outcomes may be linked to an increased rate of periprocedural complications, device failure, pacemaker implantation, or paravalvular leak. 14,15 AS severity, and thus VAC, is also correlated with myocardial fibrosis, 16 which is mostly irreversible and influences post-operative mortality 17 and heart failure. 18 This may explain that VAC continued to have a prognostic significance over the long run, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…13 The mechanisms underlying the association of VAC with post-TAVI outcomes may be linked to an increased rate of periprocedural complications, device failure, pacemaker implantation, or paravalvular leak. 14,15 AS severity, and thus VAC, is also correlated with myocardial fibrosis, 16 which is mostly irreversible and influences post-operative mortality 17 and heart failure. 18 This may explain that VAC continued to have a prognostic significance over the long run, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac CT is an important imaging modality in severe AS patients who are indicated for surgical valve replacement or transcatheter aortic valve replacement, because it provides detailed anatomic information about the aortic valve, coronary artery, ascending thoracic aorta, and LV 83). Recently, Song et al84) showed that aortic valve calcium volume score on cardiac CT was associated with severity of myocardial fibrosis in severe AS patients. Bandula et al20) showed that there was a significant correlation between both equilibrium cardiac CT - and equilibrium CMR imaging-derived ECV and percentage of histologic fibrosis (r = 0.71, p < 0.001 and r = 0.84, p < 0.0001, respectively).…”
Section: Hypertrophy Related To Increased Afterloadmentioning
confidence: 99%